In situ and Operando Raman Spectroscopy of Layered Transition Metal Oxides for Li-ion Battery Cathodes - Flores, Eibar; Novák, Petr; Berg, Erik J. (Frontiers in Energy Research, 2018)
In situ and operando Raman spectroscopy is proposed to provide unique means for deeper fundamental understanding and further development of layered transition metal LiMO2 (M = Ni, Co, Mn) oxides suitable for Li-ion battery applications. We compare several spectro-electrochemical cell designs and suggest key experimental parameters for obtaining optimum electrochemical performance and spectral quality. Studies of the most practically relevant LiMO2 compositions are exemplified with particular focus on two experimental approaches: (1) lateral and axial Raman mapping of the electrode's (near-) surface to monitor inhomogeneous electrode reactions and (2) time-dependent single-particle spectra during cycling to analyze the LixMO2 lattice dynamics as a function of lithium content. Raman Spectroscopy is claimed to provide a unique real-time probe of the M-O bonds, which are at the heart of the electrochemistry of LiMO2 oxides and govern their stability. We highlight the need for further fundamental understanding of the relationships between the spectroscopic response and oxide lattice structure with particular emphasis on the development of a theoretical framework linking the position and intensity of the Raman bands to the local LixMO2 lattice configuration. The use of complementary experimental techniques and model systems for validation also deserve further attention. Several novel LiMO2 compositions are currently being explored, especially containing dopings and coatings, and Raman spectroscopy could offer a highly dynamic and convenient tool to guide the formulation of high specific charge and long cycle life LiMO2 oxides for next-generation Li-ion battery cathodes.